VALORACIÓN DE EMPRESAS POR EL MÉTODO DE LOS RENDIMIENTOS FUTUROS - Narváez Liceras, Alejandro (2008)
Many educators and professionals of the business world have said, more than one time, that the appraisal of businesses is in great measure an art to handle the numbers according to some definite objectives. Without doubt, something can should certain in this affirmation however, this activity has a lot of thorough knowledge of the difficulties and associated problems to assign him the value “real” to a going company. This article has as object to examine diverse aspects of the appraisal of businesses applying the method of the future performances. They are explained some of the reasons by which this method is chosen, and the form is undertaken how the variables are quantified.